MENINGKATKAN KEMAMPUAN INTERPERSONAL DALAM PEMBELAJARAN TARI KREASI MELALUI MODEL PEMBELAJARAN STAD PADA SISWA USIA 15-17 TAHUN DI SANGGAR TARI CANDIK AYU - Maharani, Rejna Azhara; Deden Haerudin; Selly Oktarini (Jurnal Pendidikan Tari, 2025)
This study aims to improve interpersonal skills through the application of the cooperative learning model, Student Teams Achievement Division (STAD), in creative dance training, specifically the Merak dance. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, which consists of four stages in each cycle: (1) planning, (2) acting, (3) observing, and (4) reflecting. The research subjects were 9 training participants aged 15–17 years. Data were collected through observation and interviews, with research instruments in the form of an interpersonal skills observation sheet covering indicators of openness, empathy, positive attitude, and equality. The results showed that interpersonal skills consistently improved in each training session, from the pre-cycle to Cycle II. The average score increased from 27 in the pre-cycle to 42 in Cycle I, and reached 57 in Cycle II. The N-Gain analysis showed a score of 0.8, categorized as high. Based on these findings, the implementation of Merak dance learning through the STAD model proved effective in improving the interpersonal skills of training participants aged 15–17 at sanggar tari Candik Ayu.